Suberin isolation from cork using ionic liquids: characterisation of ensuing products - Ferreira, Rui; Garcia, Helga; Sousa, Andreia F.; Petkovic, Marija; Lamosa, Pedro; Freire, Carmen S. R.; Silvestre, Armando J. D.; Rebelo, Luís Paulo N. Luis Paulo N.; Pereira, Cristina Silva (New Journal of Chemistry, 2012)
Cholinium alkanoates, a class of benign ionic liquids, were demonstrated to efficiently extract suberin domains from cork. A detailed characterisation of the extracted material has yet to be attained. In the present study the significance of the alkylic chain length of the anion and the ionic liquid's basicity was investigated. The results obtained emphasise cholinium hexanoate's selection; it proved to be a straightforward process, also ensuring the recyclability and reusability of the ionic liquid. The extracted suberinic material has been thoroughly characterised for the first time by ATR-FTIR, NMR, GC-MS and thermal analyses. Data showed that it is mainly composed of oligomeric or polymeric aliphatic esterified structures, resulting from suberin partial cleavage. More than 40 wt% of the extracted suberinic material was found to be cross-linked. Even though, the composing monomeric units were similar to those usually identified in suberin samples obtained by the conventional extraction processes. These data pave the way for advanced studies of suberin monomers/oligomers as building-blocks for the development of novel biopolymers and biomaterials.
The following values have no corresponding Zotero field: publisher: The Royal Society of Chemistry
Keywords: Cholinium alkanoates; Cork; Extraction; suberin; suberinic materials (voyant)

Suberin: A promising renewable resource for novel macromolecular materials - Gandini, Alessandro; Pascoal Neto, Carlos; Silvestre, Armando J. D. (Progress in Polymer Science, 2006)
Suberin, an aliphatic-aromatic cross-linked natural polymer present in the outer tissues of numerous vegetable species, is discussed in terms of (i) its occurrence, particularly where it dominates the bark composition of some trees, (ii) its macromolecular structure and positioning within the cell wall, (iii) its controlled chemical splicing (depolymerization through ester cleavage), (iv) the qualitative and quantitative composition of the ensuing monomeric fragments, and (v) the exploitation of this mixture of monomers in macromolecular science, both as a possible functional additive and as a source of novel materials. The presence of terminal carboxylic and hydroxy groups and of side hydroxy and epoxy moieties on the long chains of suberin ‘‘monomers’’ makes them particularly suited as building blocks for polymers with original architectures and interesting properties
Keywords: Cork; dicarboxylic acids; hydroxyacids; long-chain aliphatic compounds; polyurethanes; suberin

Composition of Suberin Extracted upon Gradual Alkaline Methanolysis of Quercus suber L. Cork - Lopes, Marta H.; Gil, Ana M.; Silvestre, Armando J. D.; Neto, Carlos Pascoal (Journal of Agricultural and Food Chemistry, 2000)
The monomeric composition of suberin extracts obtained by gradual alkaline methanolysis of Quercus suber cork was determined by gas chromatography?mass spectrometry (GC-MS). Results show that 1-alkanols and alkanoic and α,?-alkanedioic acids are preferentially removed upon mild alkaline conditions, whereas mid-chain-modified ?-hydroxyalkanoic acids are preferentially removed under stronger alkaline conditions. Saturated ?-hydroxyalkanoic acids are found to be abundant in all suberin extracts. These results are consistent with two distinct suberin fractions with different locations in cork cell walls and/or esterification degrees. It is proposed that these fractions correlate with the two main suberin peaks in the solid state 13C NMR spectra of cork and suberin extracts. Quantitative GC-MS analysis showed that suberin monomers comprise ?30% (w/w) of the suberin extracts, the remaining comprising nonvolatile structures with high Mn values, as measured by vapor pressure osmometry. The presence of a large fraction of high molecular weight aliphatic structures in suberin extracts is supported by the corresponding NMR spectra. Keywords: Suberin; cork; Quercus suber L.; GC-MS; NMR; alkaline methanolysis
doi: 10.1021/jf9909398doi: 10.1021/jf9909398The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Alkaline methanolysis; Cork; GC-MS; NMR; Quercus suber L.; suberin